ON THE FORMATION OF FINANCIAL BODIES AND FINANCIAL POLICY OF THE KAZAKH REPUBLIC IN THE 20S OF XX CENTURY - Nurpeisova, B.; Dyussembekova, Zh. (Journal of history, 2018)
The article is devoted to the history of formation and sequential strengthening of the financial structure of Kazakhstan in the 20s of the early twentieth century. It covers some issues of the construction of a new state institution, which was designed to provide financial support to all public authorities, the national economy of the Republic, in general, all life-supporting industries in the most difficult for the time, conditions when there is a change of social order, accompanied by civil war, famine and devastation. The main stages of formation, interaction with other state bodies, financial policy, personnel potential of the financial system are analyzed. The research is based on documents and materials of archival funds, other materials are involved.